Exposure of free-ranging capybaras (Hydrochoerus hydrochaeris) to the vaccinia virus - Antunes, João Marcelo Azevedo de Paula (2020)
The aim of this study was to evaluate the possibility of free-ranging animals/hunting dogs as sources of infection in the vaccinia virus (VACV) transmission chain. Serological, cell culture and molecular assays were conducted in 56 free-ranging animals and 22 hunting dogs. ELISA/neutralizing assays showed that two (2.5%) capybaras (Hydrochoerus hydrochaeris) had anti-OPV positive antibodies, while all samples tested negative through PCR/cell culture. After being hit by cars on roads, capybaras that exhibited neither clinical signs nor any association with bovine outbreaks had neutralizing antibodies against the Orthopoxvirus, as detected through plaque-reduction neutralizing tests and ELISA. Evidence exists regarding peridomestic capybaras acting as a source of the virus and serving as a link between wild and urban environments, thus contributing to viral maintenance.